Rehabilitation and Secondary Prevention in Cardiology”, VIII Russian Scientific Conference with international participation, celebrating 40-Year anniversary of the Soviet and Russian cardiological rehabilitation, May 13-14 2009, Moscow - Article Aditorial (Российский кардиологический журнал, 2008)
.